Grey literature – grey sources? Nuancing the view on professional documentation: The case of Swedish archaeology. Issue 6 (12th October 2015) - Börjesson, Lisa
Abstract : Purpose: – The purpose of this paper is to nuance the perception about professional documentation (a.k.a. "grey literature"), assuming perception of documentation being a cultural aspect of accessibility. Design/methodology/approach: – The study explores variations within the archaeological report genre through a bibliometric analysis of source use. Source characteristics are explored as well as correlations between report authors and source originators. Statistical frequency distribution is complemented by a correspondence analysis and a k -means cluster analysis to explore patterns. The patterns are interpreted as "frames of references" and related to circumstances for archaeological work. The study also discusses source representations. Findings: – The source use patterns reveal a latent variation, not visible in the general analysis: a professional/academic frame of reference (mainly among authors affiliated with incorporated businesses and sole proprietorships) and an administrative frame of reference (mainly among authors affiliated with government agencies, foundations, and member associations) emerge. Research limitations/implications: – The study focuses on Swedish field evaluation reports. Future research could test the results in relation to other types of reports and go beyond the document perspective to explore source use in documentation practices. Social implications: – The results on variations in frames of references among report writers have implication for report readers and user. The results should also be considered in archaeology management and policy-making. On the level of source representation the results call for clarifications of vague representations and possibly omitted sources. Originality/value: – This study contextualizes archaeological information use and focuses on variations in professional archaeology which has received little previous research attention. The bibliometric approach complements previous qualitative studies of archaeological information.